Systemic biomarkers for the preclinical diagnosis of dementia. (20th October 2021) - Biarnés-Martínez, M; Hernáez, A; Subirana, I; Martínez-González, MA; Corella, D; Salas-Salvadó, J; Ros, E; Estruch, R; Fitó, M; Castañer, O
Abstract: Background: As a consequence of aging and the age-related cardiovascular risk, both of them closely associated to neurodegenerative diseases, dementia has become one of the major public health concerns for governments and the scientific and medical communities. Up to date, there isn't any front-line screening tool implemented at a population level. In this regard, we aim to assess the association of several systemic biomarkers related to neuroinflammation [lactate dehydrogenase (LDH), complement component 3, C-reactive protein, alpha-1-antitrypsin, alpha-2-macroglobulin (α2M) and pancreatic prohormone], lipid metabolism [apolipoprotein E, 24S-hydroxycholesterol], and neuronal integrity [tau protein], with dementia risk in an adult-elderly population at high cardiovascular risk. Methods: We designed a case-cohort study nested in the PREDIMED cohort (110 incident cases of dementia, 251 non-cases). Participants were at high risk for cardiovascular disease (CVD), but had no clinical CVD neither dementia at the time of enrolment. Inclusion criteria were an age of 55-80 years old and the presence of diabetes type 2 or at least 3 cardiovascular risk factors (smoking, overweight or obesity, hypertension, dyslipidemia, and family history of premature CVD). We used Cox proportional hazard models to estimate hazard ratios (HR) of the association between these nine plasma biomarkers and dementia risk adjusted for several covariates. Results: Dementia cases were older, presented higher levels of fasting glucose and were more likely to have type 2 diabetes. The prevalence of dyslipidemia and smoking in patients with dementia was lower. Dementia cases had higher levels of LDH and α2M. Higher LDH levels were associated with a higher risk of developing dementia after adjustment (HR = 1.19). Conclusions: Higher LDH plasma levels are associated with a higher risk of dementia incidence in population at high cardiovascular risk. Key messages: Higher levels of LDH are associated with higher risk of dementia incidence among adult-elderly individuals with a high cardiovascular risk profile. The early detection of this biomarker could enable an early intervention and to delay, or perhaps even prevent, the onset of clinical symptoms.